Nepal, China and 'Belt and Road Initiative': Prospects and Challenges. (September 2022) - Sharma, Samir; Chhetri, Preksha Shree
At a time when the push towards a 'decoupling' from China has gained significant traction, debates with regard to the favourability of the conditions of China–Nepal engagement within the BRI framework acquire significance. Despite being signed in 2017, it remains to be seen whether the 'terms' of the BRI framework has positive consequences for Nepal or not. Against this backdrop, and through a discussion of the larger contours of (under)development in Nepal, Nepal–China relations and perceptions of India, we argue that BRI in Nepal indicates an attempt to reframe Nepal's geo-strategic position. This assertion undergirds the pivotal role of polyamorous cooperation envisioned by Nepal—both in the context of Sino-India relations and in staking its agency towards an 'independent' foreign policy. However, this attempt, we argue, will be constrained by the concrete, unresolved issues of BRI investments in Nepal as well as by the larger power (im)balances.